2007
DOI: 10.1016/j.nbd.2007.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged angiotensin-converting enzyme inhibitor treatment on amyloid β-protein metabolism in mouse models of Alzheimer disease

Abstract: Genetic and pathologic studies have associated angiotensin-converting enzyme (ACE) with Alzheimer disease. Previously, we and others have reported that ACE degrades in vitro the amyloid β-protein (Aβ), a putative upstream initiator of Alzheimer disease. These studies support the hypothesis that deficiency in ACE-mediated Aβ proteolysis could increase Alzheimer disease risk, and raise the question of whether ACE inhibitors, a commonly prescribed class of anti-hypertensive medications, can elevate Aβ levels in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 44 publications
5
74
0
Order By: Relevance
“…Here, it was entirely appropriate to test ACE inhibitors in animal models of AD. In this particular case, several independent studies failed to show any effect of ACE inhibitors on A␤ accumulation (39,40). Together with other findings from knock-out animals (39), these pharmacological studies were instrumental in establishing that ACE is not important for A␤ degradation in vivo (at least in rodents).…”
Section: Categories Of Investigationmentioning
confidence: 79%
“…Here, it was entirely appropriate to test ACE inhibitors in animal models of AD. In this particular case, several independent studies failed to show any effect of ACE inhibitors on A␤ accumulation (39,40). Together with other findings from knock-out animals (39), these pharmacological studies were instrumental in establishing that ACE is not important for A␤ degradation in vivo (at least in rodents).…”
Section: Categories Of Investigationmentioning
confidence: 79%
“…At present, the balance of the evidence suggests that it is not. Oral administration of the widely used ACE inhibitor, captopril, to APP transgenic mice resulted in no significant elevation in cerebral Ab levels (Hemming et al 2007b). Moreover, genetic deletion of ACE failed to produce any significant elevation in steady-state levels of endogenous Ab (Table 1; Eckman et al 2006).…”
Section: Angiotensin-converting Enzymementioning
confidence: 99%
“…ACE was also expressed in the brain by resident CD45 lo-intermed ACE hi microglia. In AD + ACE 10 risk (20,(64)(65)(66)(67). Several meta-analyses have consistently found that lower serum and tissue ACE levels, as determined by an ACE gene polymorphism, were associated with a small increased risk of developing AD (68)(69)(70)(71).…”
Section: Figurementioning
confidence: 99%